Sit, Marley, sit! - Le Ny, Jeanine; Grogan, John, 1957-; Cowdrey, Richard; Lyon, Tammie (New York : Harperfestival, 2010)
Marley, a naughty puppy, goes to obedience school.
Keywords: Marley (Dog) -- Juvenile fiction; Dogs -- Juvenile fiction